Defending Ireland from the Irish: The Irish Executive’s reaction to Transatlantic Fenianism - 1864-68 - Devitt, Jerome (Trinity College Dublin, School of Histories & Humanities, Discipline of History, 2018)
This thesis examines the Irish Executive’s reaction to the threat posed by transatlantic Fenianism from the closing phase of the US Civil War to the end of Fenian activity in the year following the Rising of February/March 1867. It proposes that the Fenian conspiracy was the catalyst for a substantial development in the Executive’s ability to assert its control throughout the country in the name of maintaining state security. Its central argument is that the government’s adoption of a policy of deterrence, combined with the systematic reform of the composition and distribution of military force on the island, at first delayed, and later helped to suppress the abortive rising that eventually emerged. The Executive’s response was influenced by the suppression of the Young Ireland rising in 1848 and other imperial revolts, but needed to balance the needs of both ‘Home’ and ‘Imperial’ Defence. This set in motion a security policy that would influence the governance of Ireland throughout the remainder of the century. Methodologically, the thesis examines these actions in the light of recent developments in counterinsurgency theory and practice, and by using Michael Mann’s theory of the “Infrastructural Power of the State” as a tool to facilitate this analysis. Where possible, the thesis views these elements in a transnational context, particularly by considering the wide range of imperial experiences of senior administrators and military commanders and assessing how those experiences influenced Irish affairs. This framework adds to current knowledge by demonstrating the capacities and limitations of the mid-Victorian governance of Ireland. It does this by contrasting the stated policy goals of the Executive and assessing them against the actual actions on the ground. The thesis is structured into three broad thematic sections. The first, the ‘Civil Sphere’ examines the use of coercive legislation and policing as tools of counterinsurgency. Chapter One focuses primarily on how the suspension of Habeas Corpus was used to influence the potential insurgents and imprison those who threatened state security. Chapter Two considers how the Irish Constabulary shifted from its usual civil duties to embrace more militarized functions at a time of crisis. Chapters Three and Four in second section, the ‘Military Sphere’, examine the Army and Irish Militia. The reform and redeployment of the army for political ends and the formation of Flying Columns at the outbreak of the rising are contrasted with the implications of the suspension of the Militia’s annual training. The three chapters of the final section, the frequently overlooked ‘Naval Sphere’, examine the role of the Royal Navy, Royal Marines, and the Irish Coastguard and assess their contribution to counterinsurgency activities. While each chapter deals with a specific institution, the coordinating role of the Irish Executive is never far from the surface. The thesis concludes that without vigorous Executives, led by Lords Wodehouse and Naas respectively, to coordinate the disparate branches of state power, the suppression of Fenianism would have been significantly more problematic.
Keywords: Fenianism